A teenage girl with unexpected bleeding: Munchausen syndrome (BIRDEM Medical Journal, 2025)
Munchausen syndrome is a factitious disorder which was reported by Richard Alan John Asher for the first time in 1951. In this condition the patient intentionally produces physical or psychological signs or symptoms. Patient plays a sick role without any external incentives. Though it is a rare disease as to be found in less than 1% in clinical settings, still it should be considered as a differential diagnosis in some cases to prevent unnecessary medical expenses. Sometimes it might be found challenging to diagnose a case as Munchausen syndrome because patient may have adequate medical knowledge to skip physician’s eye for a while. We present case history of a case of 15-year-old girl, who visited outpatient department of Transfusion Medicine and Clinical Haematology with bleeding from various parts of her body. She was diagnosed as Munchausen syndrome. She got required treatment and was referred for psychological assessment and support.BIRDEM Med J 2025; 15(2): 80-82